New Frontiers in Environmental and Social Labeling - Grote, Ulrike; Basu, Arnab K.; Chau, Nancy H.; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2007)
The attractiveness of product labeling stems from their voluntary nature to achieve environmental and social goals. It is argued that through product price premia which reflect the willingness of consumers to pay more for green and socially conscious products, labels have the potential to generate changes in production techniques. In addition, labeling of products has become the preferred instrument for solving high profile trade disputes amongst members of the World Trade Organization. The contributions in this volume provide an indepth look at labeling and its relation to the governance of global trade. The book aims at bridging the research gaps related to the link between consumers$1 (Bperception of a label with their willingness to pay, the impact and the limitations of labeling in the event of food safety hazards, and the trade and development dimensions of labeling. As such, this volume presents research that constitutes a new frontier on issues related to the economics of labeling.s
Outline and Emerging Issues -- The Design of an Eco-Marketing and Labeling Program for Vehicles in Maine -- Performance-based Labeling -- Do Social Labeling NGOs Have Any Influence on Child Labor? -- Economic Analysis of Eco-Labeling: The Case of Labeled Organic Rice in Thailand -- Eco-labeling and Strategic Rivalry in Export Markets -- Science, Opportunity, Traceability, Persistence, and Political Will: Necessary Elements of Opening the U.S. Market to Avocados from Mexico -- The Labels in Agriculture, Their Impact on Trade and the Scope for International Policy Action -- Social Standards and Their Impact on Exports: Evidence from the Textiles and Ready-Made Garments Sector in Egypt -- Developing Country Responses to the Enhancement of Food Safety Standards -- Scope and Limitations for National Food Safety and Labeling Regimes in the WTO-Frame.
Keywords: Environmental management; Economic policy; Development economics; Environmental economics; Economics; Environmental Economics; Development Economics; Economic Policy; Environmental Management; Electronic books